EDUKASI PERLINDUNGAN DATA PRIBADI DALAM LAYANAN PUBLIK PADA MASYRAKAT DAERAH PEMILIHAN PAPUA - Surbakti, Feliks Prasepta Sejahtera (LPPM Universitas Nusa Mandiri, 2025)
The protection of personal data has become a critical concern in Indonesia, particularly with the increasing cases of data breaches involving healthcare platforms and government institutions. In public services, safeguarding personal data is vital to maintaining citizens’ trust in government systems. This community service program aims to enhance public and stakeholder awareness of regulations, digital technologies, and best practices in personal data protection. Activities were carried out through an educational approach, including seminars and hands-on training. The materials covered the urgency of personal data protection, relevant Indonesian regulations such as Law No. 27 of 2022, and practical digital security techniques such as two-factor authentication, full encryption, and safe internet practices. The results indicated a significant improvement in participants’ understanding of personal data protection and their ability to apply digital security measures. Participants also received technical guidance on the use of emerging technologies, including biometric authentication and secure password management. In conclusion, effective personal data protection in public services requires not only strong legal frameworks but also continuous public engagement through education and technology adoption. This program contributes to building a safer and more trustworthy digital ecosystem in Indonesia and serves as a replicable model for enhancing digital literacy in public institutions.